Analysis Of Land Ownership Disputes By Foreign Nationals Based On Wills: Case Study Of Supreme Court Decision No. 1134/Pdt/2009 In The Perspective Of International Civil Law - Putri Dwi Ramadhani, Shahnata; Arum Prastyanti, Rina (Mutiara: Multidiciplinary Scientifict Journal, 2024)
Land ownership in Indonesia is strictly regulated, especially for foreigners, through the Basic Agrarian Law (UUPA). This legal foundation limits the rights of foreigners in terms of land ownership, especially property rights, according to Article 21 of the UUPA. The case of Supreme Court Decision No. 1134/Pdt/2009 provides a clear example of how the recognition of inheritance rights for foreigners on land can lead to complicated legal issues. The method of this research is normative juridical with a statutory and case approach. This method focuses on the analysis of Supreme Court Decision No. 1134/PDT/2009 on land ownership disputes between citizens and foreigners based on wills. Primary data was obtained through court decisions and related laws and regulations, such as the UUPA, while secondary data was through legal literature, and legal periodicals In Supreme Court Decision No. 1134/Pdt/2009, legal considerations regarding land ownership by foreign nationals (WNA) based on wills are the basis of juridical considerations in the case. one of the basic principles that apply in international civil law is lex situs or the law that applies in the country where the land object is located. Based on the principle of lex situs, any breach or agreement relating to property must be subject to the law of the country where the property is located. According to an analysis of Supreme Court decision No. 1134/Pdt/2009, although foreign nationals can receive land through wills, Indonesian agrarian law explicitly prohibits foreigners from owning land. This creates a conflict between domestic law and the legal principles of international property rights protection. Decision No. 1134/Pdt/2009 became an important reference in Indonesian international civil and agrarian law.